GE_GERICHTE C/3416/2018 vom 19. Oktober 2018 - GE Cour de justice (2018)
MAINLEVÉE DÉFINITIVE ; DROIT D'ÊTRE ENTENDU ; TITRE EXÉCUTOIRE ; CESSION DE CRÉANCE(CO) ; OBLIGATION D'ENTRETIEN | LP.80; Cst.29.al2; LARPA.2; LARPA.101; CO.166; CO.167